Comparison of Diagnostic Accuracy of Digital Mammography, Digital Breast Tomosynthesis and Contrast Enhanced Mammography in the Preoperative Assessment of BI-RADS III and above Lesions in Dense Breasts: A Cross-sectional Study - Jini Joseph; KG Ramakrishnan; Rekha Narayanan (Journal of Clinical and Diagnostic Research)
Introduction: Women belonging to breast density category C and D have high mammographic density and are at an increased risk for developing breast cancer. Although mammogram is the gold standard technique for the detection and diagnosis of breast cancer, extremely dense breasts-due to reduced contrast between tumours and surrounding tissue-pose significant limitations in the identification and diagnosis. This limitation has been overcome by introduction of 3D Digital Breast Tomosynthesis (3D DBT) and other newer imaging modalities like Contrast-Enhanced Mammography (CEM), breast ultrasound and Magnetic Resonance Imaging (MRI). Aim: To compare the diagnostic accuracy of CEM, Digital Mammography (DM), and DBT in assessing cancer detection rate in dense breasts. Materials and Methods: A cross-sectional study was conducted with a sample size of 53 patients in the Department of Radiodiagnosis at Malabar Institute of Medical Sciences (MIMS) Calicut, Kerala, India, from October 2022 to September 2023. DM, DBT, and CEM images were taken for each patient and were visually assessed to identify primary and satellite lesions, measure the size of the index lesions and classify them according to Breast Imaging Reporting and Data System (BI-RADS) American College of Radiology (ACR) lexicon category. Results were then compared to histopathology. Categorical variables were summarised in terms of frequency with % and tested using Chi-square test. Continuous variables were summarised as mean±standard deviation or median with interquartile range. Results: A total of 53 subjects were included in the final analysis, with an average age of 51.7±11.5 years. Among three modalities, CEM proved best for maximum Cancer Detection Rate (CDR), accounting for 100% sensitivity, an 81% Positive Predictive Value (PPV), and 81% diagnostic accuracy for detecting malignancy. Whereas DBT had 79% diagnostic accuracy and DM had 73.5% diagnostic accuracy for detecting malignancy. Mean volume of the lesions evaluated by histopathology was 5.6, while those measured by DM, DBT, and CEM were 7.8, 6.4, and 6.2. All three modalities overestimated lesion sizes compared to histopathology, with CEM showing a smaller difference. In case of additional lesion evaluation, CEM detected 16 more cases that were undetected on DM and 12 more cases that were undetected on DBT. Conclusion: CEM is superior diagnostic modality in evaluation of cancer detection in dense breasts and can be a suitable alternative for DM and DBT in dense breasts with certain limitations.